2011
DOI: 10.1007/s10071-011-0454-x
|View full text |Cite
|
Sign up to set email alerts
|

Finding the best angle: pigeons (Columba livia) weight angular information more heavily than relative wall length in an open-field geometry task

Abstract: Pigeons were trained to locate food in two geometrically equivalent corners of a parallelogram-shaped enclosure. Both the angular amplitude of the corners and the length of the walls alone were sufficient for successfully completing the task. Following training, birds were tested in three separate conditions that manipulated the geometric information available. During tests in both a rectangular-shaped enclosure that preserved the wall length information but not the angular amplitude, and a rhombus-shaped encl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
(36 reference statements)
3
9
0
Order By: Relevance
“…Although one might argue that participants used the principal axis rather than angles in the rhombus environment, the salience of the principal axis was drastically reduced in the rhombus as compared to the rectangle, and therefore the use of a principal axis strategy should have led to a difference in accuracy between these tests. However, the present results showing that humans performed equally well in the rhombus and rectangle test environments are consistent with those found in similar tests with both pigeons (Lubyk & Spetch, 2011) and domestic chicks (Tommasi & Polli, 2004). This finding is interesting and suggests considerable cross-species generality.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Although one might argue that participants used the principal axis rather than angles in the rhombus environment, the salience of the principal axis was drastically reduced in the rhombus as compared to the rectangle, and therefore the use of a principal axis strategy should have led to a difference in accuracy between these tests. However, the present results showing that humans performed equally well in the rhombus and rectangle test environments are consistent with those found in similar tests with both pigeons (Lubyk & Spetch, 2011) and domestic chicks (Tommasi & Polli, 2004). This finding is interesting and suggests considerable cross-species generality.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, preference for the correct angular information was similar, whether participants were trained to find an acute corner (60°) or an obtuse corner (120°). These results are also consistent with those reported for pigeons (Lubyk & Spetch, 2011), but not for chicks (Tommasi & Polli, 2004); chicks trained to locate acute angles chose the correct angles, whereas chicks trained to locate obtuse angles chose the correct relative wall lengths. Tommasi and Polli suggested that acute angles may be more visually salient than obtuse angles, and therefore, in a conflict situation, chicks would rate the acute angle higher than relative wall length but would rate the obtuse angle lower than the wall length information.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A growing number of studies have shown that reorientation by human and non-human animals is highly sensitive to alterations in local geometry and our results add to this body of research [7], [10], [11], [28], [29]. During testing in the L-shaped environment, participants directed the majority of their searches to the corners that matched the medial axes of the training environment.…”
Section: Discussionmentioning
confidence: 52%